Proyecto de creación de una residencia universitaria para los estudiantes de la ESPOL - Zambrano Farias, Jéssica Cristina (2010)
The following grade project will be based on the creation of a university residence for students from other provinces seeking accommodation in the city of Guayaquil. In chapter one will analyze key factors such as economic and social that influence the creation of the residence, and some information on the number of students who arrive each year in Guayaquil for study purposes. In chapter two will be carried out market research which specifies the type of sampling and its conclusions. Other important variables to be analyzed are the strategic plan, SWOT analysis and marketing plan and more. In chapter three, there will be technical and organizational study which describes the design, distribution and requirements. In the organizational study will be known the number of employees and workers for residency.   Chapter four will be based on financial analysis to determine the feasibility and profitability of the draft agreement to develop a sensitivity analysis of projected cash flow for a period of 5 years.